Yersinia Enterocolitis May Mimic Appendicitis: 12 Years of Experience in a Single Tertiary Center - Fernandes,Sara (2021)
Abstract: Introduction: Yersinia enterocolitica infection is a zoonotic disease that varies from self-limited gastroenteritis to more severe forms. Its propensity to affect the terminal ileum and to spread to regional lymph nodes explains the potential misdiagnosis with appendicitis. Methods: We reviewed the Y. enterocolitica infection cases in a pediatric population for the last 12 years. Results: There were 11 cases of Y. enterocolitica infection in the selected period. Four patients had a suspected surgical diagnosis: 1 intussusception, 3 acute appendicitis. Patients who presented with appendicitis-like features were older, whereas younger children most commonly presented with diarrhea and fever. Ultrasound and abdominal computed tomography (CT) were performed in appendicitis-like patients and ruled out appendicitis in 2 of the 3 cases. The only patient submitted to surgery had abnormal CT findings and an important risk factor for this infection that was not recognized at presentation. Conclusion: This condition should be considered in patients with known risk factors (such as iron overload) and with the right epidemiological setting when presenting with abdominal symptoms. The suspicion of this diagnosis in these particular cases might obviate unnecessary surgical interventions.